1996
DOI: 10.1021/jp960214w
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effect on Ultrafast Intermolecular Electron Transfer

Abstract: Deuterium isotope effects on ultrafast intermolecular electron transfer (ET) from electron-donating solvents such as aniline (AN) and N,N-dimethylaniline (DMA) to a number of excited (S 1 ) coumarin dyes have been investigated by a femtosecond fluorescence up-conversion technique. We carry out investigations using both normal and deuterated solvents and normal and deuterated coumarin dyes. With perdeuterated AN (AN-d 7 ) or amino-deuterated AN (AN-d 2 ), we observe almost the same extent of reduction in the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
143
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(156 citation statements)
references
References 79 publications
13
143
0
Order By: Relevance
“…51 Yoshihara and co-workers first reported that in liquid DMA (N,N-dimethylaniline) PET exhibits a component faster than the solvation time. [52][53][54] Interestingly, even for ultrafast PET, they observed a bell-shaped dependence of PET rate on free-energy change (ÁG) and thus detected the so called Marcus inverted region. [52][53][54] Bagchi and Gayathri developed a non-Markovian model and correlated the highly non-exponential ET process with the highly non-exponential solvation dynamics.…”
Section: Proton and Electron Transfer In A Confined Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…51 Yoshihara and co-workers first reported that in liquid DMA (N,N-dimethylaniline) PET exhibits a component faster than the solvation time. [52][53][54] Interestingly, even for ultrafast PET, they observed a bell-shaped dependence of PET rate on free-energy change (ÁG) and thus detected the so called Marcus inverted region. [52][53][54] Bagchi and Gayathri developed a non-Markovian model and correlated the highly non-exponential ET process with the highly non-exponential solvation dynamics.…”
Section: Proton and Electron Transfer In A Confined Systemmentioning
confidence: 99%
“…[52][53][54] Interestingly, even for ultrafast PET, they observed a bell-shaped dependence of PET rate on free-energy change (ÁG) and thus detected the so called Marcus inverted region. [52][53][54] Bagchi and Gayathri developed a non-Markovian model and correlated the highly non-exponential ET process with the highly non-exponential solvation dynamics. 55 They noted that in most solvents, the solvation dynamics consist of an ultrafast sub-picosecond inertial component and a slower component in tens of picosecond.…”
Section: Proton and Electron Transfer In A Confined Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ultrafast intermolecular electron transfer process the donor and acceptors are in contact to each other and the diffusion is not necessary here. ET in this case is much faster than the solvation dynamics [11][12][13]. On the other hand under diffusive condition in the homogeneous medium [26,27] the donor and acceptor are separated by solvent molecules and the diffusion processes control the ET rate.…”
Section: Introductionmentioning
confidence: 96%
“…Both theoretical and experimental investigations have been carried out on the dynamical aspect of the electron transfer (ET) [3][4][5][6][7][8][9][10][11][12][13]. Most of these investigations, so far have been carried out are either in neat solvent where the solvent acts as a donor or under diffusive condition where the solvent is non-interacting and reactants have to diffuse before ET takes place [11][12][13]. While ET processes in the homogeneous medium are well known, only a limited works have been performed in organized media such as micelles [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%